2017
DOI: 10.5606/tgkdc.dergisi.2017.13748
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of zileuton: a 5-lipoxygenase inhibitor against myocardial ischemia/reperfusion injury

Abstract: ÖZAmaç: Bu çalışmada zileuton'un miyokardiyal iskemi/ reperfüzyon hasarı ve iskemi ile uyarılan ventriküler aritmiler üzerine olan etkileri değerlendirildi ve 5-lipoksigenaz yolağının miyokardiyal iskemi/reperfüzyon hasarının patofizyolojisindeki rolü araştırıldı. Ça lış mapla nı:Anestezi altındaki sıçanlarda, miyokardiyal iskemi 120 dakikalık reperfüzyon periyodundan önce sol ana koroner arterin 30 dakikalık ligasyonu ile oluşturuldu. Zileuton 3 ve 10 mg/kg'lik dozlarda ligasyondan 15 dakika önce verildi. Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Patients with worse left ventricular functions, previous history of cardiac surgery or long duration of crossclamp are expected to benefit more significantly from effects of carnitine. [11][12][13][14][15][16][17][18][19] Furthermore, the current study showed that elevated levels of CK, CK-MB, and Troponin-T decreased earlier and more obviously in patients receiving carnitine. This finding suggests that myocardium protected by carnitine starts to recover before the other groups.…”
Section: Discussionmentioning
confidence: 81%
“…Patients with worse left ventricular functions, previous history of cardiac surgery or long duration of crossclamp are expected to benefit more significantly from effects of carnitine. [11][12][13][14][15][16][17][18][19] Furthermore, the current study showed that elevated levels of CK, CK-MB, and Troponin-T decreased earlier and more obviously in patients receiving carnitine. This finding suggests that myocardium protected by carnitine starts to recover before the other groups.…”
Section: Discussionmentioning
confidence: 81%
“…Bu tür aritmilere iskemi/reperfüzyon (I/R) aritmileri denir (1). I/R aritmilerinin oluşumunun önlenmesi için yeni ve etkili tedavi yolları bulmak amacıyla deneysel hayvan modellerinde araştırmalar yapılmaktadır (2,3) Kannabinoid reseptörleri ve endokannabinoidleri içeren endokonabinoid sistem iştah, ağrı duyumu, duygu durum ve bellek gibi etkinliklerde görev alır (4). Kannabinoidler farmakolojik olarak aktif moleküllerdir.…”
unclassified